Pengaruh Direktur Berkeahlian Keuangan, Nilai Perusahaan, Ukuran Perusahaan Terhadap Penghindaran Pajak di Industri Jasa Sub Sektor Farmasi yang Terdaftar di Bei 2016-2022 - Evita Lendani; Ickhsanto Wahyudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to determine and analyze the influence of directors with financial expertise, company value and company size on tax avoidance listed on the Indonesia Stock Exchange for the 2016-2022 period. The independent variables used in this research are directors with financial expertise, company value and company size on the dependent variable, namely tax avoidance. The method for collecting data uses a purposive sampling technique with a total of 112 data from the Pharmaceutical Industry. Secondary data was obtained from the company's official website and the Indonesian Stock Exchange. The method used in this research is the multiple linear regression analysis method. Based on the results of this research, it shows that the director variable with financial expertise has a positive and significant effect on tax avoidance, company value proves that it has no effect on tax avoidance and company size has no effect on tax avoidance. (Added research contribution & accounting results)